Mature murine supraspinatus tendons demonstrate regional differences in multiscale structure, function and gene expression - Michael S. DiStefano; Stephanie N. Weiss; Courtney A. Nuss; Rebecca L. Betts; Biao Han; Andrew F. Kuntz; Louis J. Soslowsky (PLoS ONE, 2025)
The hierarchical structure of tendon dictates its ability to effectively transmit loads from muscle to bone. Tendon- and site-specific differences in mechanical loading result in the establishment and remodeling of structure, as well as associated changes in composition throughout development and healing. Previous work has demonstrated region-specific differences in the response of collagen fibrils to mechanical loading within the insertion region and midsubstance regions of mouse supraspinatus tendons using atomic force microscopy. However, multiscale structure, function, and gene expression differences between the insertion and midsubstance of the supraspinatus tendon have not yet been linked together in a comprehensive study. Therefore, the purpose of this study was to elucidate site-specific hierarchical structure, function, and gene expression differences in mouse supraspinatus tendons. Supraspinatus tendons from day 150 wild-type C57BL/6 mice were harvested for regional mechanics, histology, transmission electron microscopy (TEM), and quantitative polymerase chain reaction (qPCR). Mechanical testing revealed that the midsubstance region demonstrated a greater modulus and increased collagen fiber realignment compared to the insertion region. Histological scoring demonstrated greater cellularity and more rounded cells in the insertion region. TEM analysis showed differences in collagen fibril diameter distributions between the two regions, with a shift towards smaller diameters observed at the insertion region. Gene expression analysis identified several genes that were differentially expressed between regions, with principal component analysis revealing distinct clustering based on region. These findings provide insight into the regional heterogeneity of the supraspinatus tendon and underscore the importance of considering these differences in the context of tendon injury and repair, contributing to a better understanding of tendon structure-function and guiding future studies aimed at elucidating the mechanisms underlying tendon pathology.